Effect of calcination temperature on catalytic properties of Au/Fe2O3 catalysts in CO-PROX. (16th November 2016) - Ayastuy, J.L.; Gurbani, A.; Gutiérrez-Ortiz, M.A.
Abstract: Au/α-Fe2 O3 catalysts have been prepared by deposition-precipitation. The support α-Fe2 O3 has been previously synthesized by precipitation technique. The effect of thermal treatment on structural, morphological and redox properties of Au/α-Fe2 O3 samples have been thoroughly studied for the samples calcined at 150, 200 and 300 °C, together with a non-calcined sample. Their catalytic activity toward CO oxidation in the presence of hydrogen (CO-PROX) has been tested. The results showed that the gold particle size and surface adsorbed oxygen changed with the calcination temperature, being the minimum for the sample calcined at 200 °C. There was not detected cationic gold by X-ray photoelectron spectroscopy (XPS) in none of the samples. The presence of gold promoted notably the reduction of the iron oxide. The highest activity for CO-PROX was achieved by the non-calcined catalysts (simply dried at 110 °C), while the sample calcined at 200 °C was the least active. The catalysts activity was assigned to the gold particle size and surface adsorbed oxygen. Highlights: Hematite supports are synthesized and used as support for gold. Calcination at 200 °C leads to the smallest gold particles. The non-calcined catalysts are the most active in CO-PROX. The activity in CO-PROX is correlated to the adsorbed oxygen.